2017
DOI: 10.22226/2410-3535-2017-4-345-349
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of NbTi superconducting alloy

Abstract: A superconducting multifilament wire made of Nb -60 at.% Ti alloy was investigated by methods of atom probe / field ion microscopy (APFIM), three-dimensional atom probe (3DAP), high resolution electron microscopy (HREM) and computer simulation. The results of the APFIM and HREM analysis suggest that the specimens contain two phases having bcc (β-phase) and hcp (α-phase) structures. Mesoscopic and nanoscale heterogeneities of element concentration in β-phase were observed. Atom probe analyses of annealed NbTi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Under the influence of the thermomechanical treatment, α-Ti precipitates develop in the β phase in the NbTi alloys [ [1] , [2] , [3] ]. The number of precipitates increases by increasing the heat treatment temperature; The effect is similar if the period of heat treatments increases at a constant temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the influence of the thermomechanical treatment, α-Ti precipitates develop in the β phase in the NbTi alloys [ [1] , [2] , [3] ]. The number of precipitates increases by increasing the heat treatment temperature; The effect is similar if the period of heat treatments increases at a constant temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Boenisch et al [ 29 ] investigated the thermal stability of NbTi alloys in a wide concentration range. Moon et al [ 30 ] and Kim et al [ 31 ] showed the relationship between the initial structure and the critical current density, while other authors observed changes in the microstructure due to various external influences [ 2 , 6 , [32] , [33] , [34] ]. Storozhilov et al [ 35 ] investigated the effect of severe plastic deformation on the decomposition of supersaturated solid solution in Nb–48.5 wt % Ti.…”
Section: Introductionmentioning
confidence: 99%